[PP.19.11] COMPUTATIONAL ASSESSMENT OF MODEL BASED WAVE SEPARATION USING A DATABASE OF VIRTUAL SUBJECTS. (September 2017) - Hametner, B.; Schneider, M.; Parragh, S.; Wassertheurer, S.
Abstract : Objective: An important area of interest in arterial pulse wave analysis is the quantification of arterial wave reflection. It can be achieved by wave separation analysis (WSA) if both the aortic pressure waveform and the aortic flow waveform are known. For better applicability, several mathematical models have been established to estimate aortic flow solely based on pressure waveforms. The aim of this study is to investigate and verify the model based wave separation of the ARCSolver method on virtual pulse wave measurements. Design and method: The study is based on a virtual database generated via simulations at the King's College London. Seven cardiac and arterial parameters were varied within physiological healthy ranges, leading to a total of 3325 virtual healthy patients. Hemodynamic data is available at 11 locations within the arterial tree. For assessing the ARCSolver computationally, this method was used to perform WSA based on the aortic root pressure waveforms of the virtual patients. As a reference, the values of WSA using both the pressure waveforms and flow waveforms (scaled to 100 arbitrary units) provided by the virtual database were taken. For evaluating the performance of the modeling approach, the results of wave separation analysis using the mathematical model of the ARCSolver were compared against the reference. Results: The investigated parameters showed a good overall agreement between the model based method and the reference, see table. Mean differences and standard deviations were −0.05 ± 0.02 AU for characteristic impedance, −3.93 ± 1.79 mmHg for forward pressure amplitude, 1.37 ± 1.56 mmHg for backward pressure amplitude and 12.42 ± 4.88% for reflection magnitude. Conclusions: The results indicate that the mathematical flow model of the ARCSolver method is a feasible surrogate for a measured flow waveform and provides a reasonable way to assess arterial wave reflection non-invasively. Figure. No caption available.